Message - Alexander, Dr. Idoko (Universal Journal of Pharmaceutical Research, 2025)
Today, the world is seeking for solutions to the various health challenges affecting social and economic status of individual, cooperate organization and the government. No doubt, Universal Journal of Pharmaceutical Research (UJPR) continues to make remarkable strides in sciences, allied sciences, and especially pharmaceutical related, exploring marine organisms, bacteria, and plants, for there medicinal potentials in disease and health management.Our appreciation goes to all authors and the editorial team for the achievements UJPR has made in publishing up to volume 9 issue 5. This is a testament of the resilience, cooperation, hard work, and thoroughness in the process of manuscript handling through peer review to publication. At nine, UJPR has formed a solid foundation via visibility to global readership through open access and the current indexing services such as cross ref, American Chemical Society, ROAD, Sherpa Romeo, EZB, ZDB, WIKIDATA, OPENALEX, FATCAT, and other academic and education platforms such Research gate and Google scholar. Concerted efforts are ongoing in making sure UJPR is Scopus indexed. This goal surely will be achieved in no time as more ground-breaking research are published in UJPR host, resulting in greater accessibility, visibility, global readership, and increased citation of our published contents. UJPR has over the years supported the screening and discovery of plant-based chemicals possessing medicinal properties and onward drug design synthesized in the lab by standardized methods and techniques for health management. As a follow up, a promising and impactful area with health driven solution in drug discovery and design in the exploration of plant/natural products-based, using computer aided techniques is emerging. This emerging area is an open area for interdisciplinary collaboration for novel, innovative and ground breaking drug discovery and design, with possible patenting. Such collaboration may include the natural products chemists, biochemists, pharmacists, bioinformatics, pharmacologists, computer scientists, microbiologists, etc. Drug discovery and design to commercially available products involve a complex process of collaborative efforts. In drug design by docking, a hit chemical compoundscreened from a library of other chemical compounds, which has a higher or same binding affinity (kcal/mol) with a standard (synthetic) drug, and fits to a specific pocket(active site) on a protein target, with chemical and geometrical stability is selected. A quick mention of the immerse contribution of UJPR to knowledge reveals the journal’s focus in publishing quality articles, keeping a track record of the rigorous and seamless manuscript review process. Authors and reviewers are applauded for keeping to the article-making-process, and are encouraged to continue in upholding to the journal’s standard. As authors, a provoking and challenging concern is engaging in research with solution driven, leaving a mark in the sands of time, with real-life applications. We earnestly aspire to be globally recognizedamong the top-ranking publishing journal, with high impact factor, and continue to encourage authors across the continents of the world to consider sending their manuscript to UJPR for consideration, and possible publication in our subsequent volumes and issues.